DEVELOPMENT OF ELECTRONIC STUDENT WORKSHEETS (E-LKPD) BASED ON DISCOVERY LEARNING ON ECOSYSTEM MATERIAL FOR GRADE X SENIOR HIGH SCHOOL - Leni Marlina; Evi Suryawati; Fitra Suzanti (Yayasan Amanah Nur Aman, 2026)
This study aims to determine the validity and practicality of Electronic Student Worksheets (E-LKPD) based on Discovery Learning on ecosystem material for Grade X senior high school. The research method used was Research and Development (R&D) with the ADDIE development model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. In this development research, the product developed was a learning resource in the form of Electronic Student Worksheets (E-LKPD) based on the Discovery Learning (DL) model on ecosystem material for Grade X senior high school. This development research was conducted only up to the development stage, which produced an E-LKPD that had been revised based on input from experts. The results of the development of the Discovery Learning–based E-LKPD on ecosystem material showed that the media expert validation categorized the E-LKPD as very valid with an average score of 3.70, while the material expert validation categorized it as very valid with an average score of 3.32. The results of the first trial stage obtained an average score of 3.78 in the very good category. The results of the second trial stage obtained an average score of 3.68 in the very good category. Overall, the Discovery Learning–based E-LKPD on ecosystem material that was developed met the criteria of validity and practicality, so it can be used as electronic teaching material to support active and interactive Biology learning in line with the demands of the Merdeka Curriculum.